2x-3=3(1-x)

Simple and best practice solution for 2x-3=3(1-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-3=3(1-x) equation:


Simplifying
2x + -3 = 3(1 + -1x)

Reorder the terms:
-3 + 2x = 3(1 + -1x)
-3 + 2x = (1 * 3 + -1x * 3)
-3 + 2x = (3 + -3x)

Solving
-3 + 2x = 3 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-3 + 2x + 3x = 3 + -3x + 3x

Combine like terms: 2x + 3x = 5x
-3 + 5x = 3 + -3x + 3x

Combine like terms: -3x + 3x = 0
-3 + 5x = 3 + 0
-3 + 5x = 3

Add '3' to each side of the equation.
-3 + 3 + 5x = 3 + 3

Combine like terms: -3 + 3 = 0
0 + 5x = 3 + 3
5x = 3 + 3

Combine like terms: 3 + 3 = 6
5x = 6

Divide each side by '5'.
x = 1.2

Simplifying
x = 1.2

See similar equations:

| 950+700+5x=800+400+10x | | 7/8=y-1/6 | | x=60x+259240 | | 12+4(z-3)=-5z+5 | | 1.4(z+0.5)=0.7(z-13) | | 3/2c+4=15 | | 5x^2+28+15=0 | | (-20/30)27/30 | | -5x-19=-13 | | 5*3/4*1/3 | | 2x(-3)=6 | | 7b/4+5=54 | | 12-2(7+2t)=2(t-1) | | 5x^2=42x+27 | | 3y+x=-16 | | 3y+x=-16 | | (4x-5)/(3x+7) | | 4(4-8y)-y=3y+7 | | 2/3c+4=15 | | f(x)=-3 | | 8=3c-7 | | 3x+1/4=4x+3/4 | | 2x^2-27x+168=0 | | 3y+14=5y | | 10x+9=3(3x+2) | | x^4-10x^2+40=0 | | U-3/u-2=4/u+4 | | 59x=-2-1+3 | | v+5/6v-1/6=(3/8v+1/4) | | -6(n+2)+13=-3n-8 | | 5g+11=-3 | | -2x+10-4=6 |

Equations solver categories